Characterization of the DNA molecular sequence of complete plastid genome of Paeonia rockii subsp. taibaishanica, an endemic species in China. Issue 9 (2nd September 2021) - Dong, Peng-Bin; Zhang, Li; Lu, Zhao-Ping; Wang, Yuan; Song, Xiao-Yu; Wang, Jiu-Xia; He, Dan; Lei, Xiao-Feng; Wang, Ma-Li; Fang, Min-Feng; Li, Zhong-Hu
Abstract: Paeonia rockii subsp. taibaishanica (Paeoniaceae), one of the tree peony species, is endemic to the Qinling Mountains in central China. In this study, we characterized its whole plastid genome sequence using the Illumina sequencing platform. The complete plastid genome size of P. rockii subsp. taibaishanica is 153, 368 bp in length, including a large single copy (LSC) region of 85, 030 bp, a small single copy (SSC) region of 17, 042 bp, and a pair of inverted repeats (IRs) of 25, 648 bp. The genome contains 131 genes, including 83 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The GC contents in chloroplast genome, LSC region, SSC region, and IR region were 38.3%, 36.6%, 32.6%, and 43.1%, respectively. A total of 16 species are used to construct the phylogenetic tree of Paeoniaceae, the results showed that P. rockii subsp . taibaishanica is more closely related with congeneric Paeonia suffruticosa and Paeonia ostii, these species were clustered into a clade with high bootstrap support.